Isomer‐Selective Generation and Spectroscopic Characterization of Picolyl Radicals. Issue 27 (6th June 2017) - Reusch, Engelbert; Holzmeier, Fabian; Constantinidis, Philipp; Hemberger, Patrick; Fischer, Ingo
Abstract: Nitrogen‐containing resonance‐stabilized radicals such as the picolyl radical are important in combustion chemistry and astrochemistry. They have only been scarcely studied because an isomer‐selective generation is often difficult. Herein, we present threshold photoelectron spectra of the three picolyl radical isomers, C6 H6 N, that were obtained with synchrotron radiation. The radicals were selectively generated by flash pyrolysis from aminomethylpyridine precursors through deamination. Ionization energies of 7.70, 7.59, and 8.01 eV were determined for 2‐, 3‐, and 4‐picolyl, respectively. The observed vibrational structure was assigned to an in‐plane deformation mode of the aromatic ring. The spectroscopic insight gained in this study can be used to distinguish different picolyl isomers in on‐line combustion analysis, for example. Abstract : The three isomers of the picolyl radical, C6 H6 N, were generated from aminomethylpyridine precursors by pyrolysis and characterized by threshold photoelectron spectroscopy with synchrotron radiation.